Numerical Simulation of Projectile Oblique Impact on Microspacecraft Structure - Zhiyuan Zhang; Runqiang Chi; Baojun Pang; Gongshun Guan (International Journal of Aerospace Engineering)
In the present study, the microspacecraft bulkhead was reduced to the double honeycomb panel, and the projectile oblique hypervelocity impact on the double honeycomb panel was simulated. The distribution of the debris cloud and the damage of a honeycomb sandwich panel were investigated when the incident angles were set to be 60°, 45°, and 30°. The results showed that as incident angle decreased, the distribution of debris cloud was increased gradually, while the maximum perforation size of the rear face sheet was firstly increased with the decrease of the incident angle and then decreased. On the other hand, the damage area and the damage degree of the front face sheet of the second honeycomb panel layer were increased with the decrease of the incident angle. Finally, the critical angle of front and rear face sheets of the honeycomb sandwich panel was obtained under oblique hypervelocity impact.